Influence of the TorD signal peptide chaperone on Tat-dependent protein translocation. - Umesh K Bageshwar; Antara DattaGupta; Siegfried M Musser (PLoS ONE)
The twin-arginine translocation (Tat) pathway transports folded proteins across energetic membranes. Numerous Tat substrates contain co-factors that are inserted before transport with the assistance of redox enzyme maturation proteins (REMPs), which bind to the signal peptide of precursor proteins. How signal peptides are transferred from a REMP to a binding site on the Tat receptor complex remains unknown. Since the signal peptide mediates both interactions, possibilities include: i) a coordinated hand-off mechanism; or ii) a diffusional search after REMP dissociation. We investigated the binding interaction between substrates containing the TorA signal peptide (spTorA) and its cognate REMP, TorD, and the effect of TorD on the in vitro transport of such substrates. We found that Escherichia coli TorD is predominantly a monomer at low micromolar concentrations (dimerization KD > 50 μM), and this monomer binds reversibly to spTorA (KD ≈ 1 μM). While TorD binds to membranes (KD ≈ 100 nM), it has no apparent affinity for Tat translocons and it inhibits binding of a precursor substrate to the membrane. TorD has a minimal effect on substrate transport by the Tat system, being mildly inhibitory at high concentrations. These data are consistent with a model in which the REMP-bound signal peptide is shielded from recognition by the Tat translocon, and spontaneous dissociation of the REMP allows the substrate to engage the Tat machinery. Thus, the REMP does not assist with targeting to the Tat translocon, but rather temporarily shields the signal peptide.